PEMBENTUKAN ASAM HUMAT DAN FULVAT SELAMA PEMBUATAN KOMPOS JERAMI PADI - A Agustian (Jurnal Solum, 2004)
Production of humic substances during the composting of organic matter becomes one criterion of compost quality. The objectives of this study were to measure and quantify the amounts of humic substances produced during the composting of rice straw by commercial decomposer, Effective Microorganism 4 (EM4). The experiment was carried out by using twenty kilograms of rice straw with C/N ratio 105 and containing 32.28% of cellulose and 4.48% lignin. The treatment essayed was the quantity EM4 applied i.e 10, 20, 30 ml and without inoculation as control. Experimental design used was Completely Randomized Design with three replications. Parameters observed are C/N ratio, humic acid, fulvic acid, and humification ratio. The results clearly showed that the increase of EM4 applied was closely related with the sum of humic substances, humic acid, and fulvic acid produced. The significance results were observed after 60 days applying compost with 30 ml EM4. It could be concluded that the quantity of EM4 applied to determine the rate of compost maturity as indicated by the value of humification ratio, was significantly different. On the other hand, the low contents of lignin in rice straw might also determine humic and fulvic acid formation.